Larval Fish Assemblages and Distribution Patterns in the Zhongsha Atoll (Macclesfield Bank, South China Sea) - Huang, Delian; Chen, Jing; Xu, Lei; Wang, Xuehui; Ning, Jiajia; Li, Yafang; Wang, Lianggen; Liu, Shuangshuang; Lin, Zhaojin; Du, Feiyan (Frontiers in Marine Science, 2022)
The remote coral reef in the deep sea is one of the most important nursery grounds for many marine fishes in the South China Sea. Diversity studies on larval fishes in this area are few, and the fish information on the coral reefs ecosystem is lacking. In this study, larval fishes were sampled during the summer of 2019 from the Zhongsha Atoll in the South China Sea and identified using DNA barcodes for the first time. Ninety-five larval fish species were recognized, belonging to 37 families and 12 orders based on morphological classification and DNA barcoding identification. The larval fish collected could be assigned to three categories as reef-associated, deep-sea, and pelagic. Most of the species were small fish with low commercial value but would play an essential role in the coral reef ecosystem. Some commercial fishes, including Auxis thazard, Euthynnus affinis, Sarda orientalis, Decapterus macarellus, Lutjanus viridis, and Centropyge vrolikii, were the dominant species higher than 2% total catch. The larval fish assemblage showed distinct spatial differences responding well with the geographical conditions. The most reef-associated fish occurred inside the Atoll, and the abyssal fish presented near the edge. In addition, larval fish spread over from the southwest to northeast may reflect the oceanography effect.